On the performance of the minimum VaR portfolio - Durand, Robert; Gould, John; Maller, R. (Routledge, 2010)
Alexander and Baptista (2002) develop the concept of mean-VaR efficiency for portfolios and demonstrate its very close connection with mean-variance efficiency. In particular, they identify the minimum VaR portfolio as a special type of mean-variance efficient portfolio. Our empirical analysis finds that, for commonly used VaR breach probabilities, minimum VaR portfolios yield ex post returns that conform well with the specified VaR breach probabilities and with return/risk expectations. These results provide a considerable extension of evidence supporting the empirical validity and tractability of the mean-VaR efficiency concept.